CXC Chemokine/Receptor Axis Profile and Metastasis in Prostate Cancer - Nagaya, Naoya; Lee, Geun Taek; Horie, Shigeo; Kim, Isaac Yi (Frontiers in Molecular Biosciences, 2020)
In this study, the effects of the CXC chemokine/receptor axis on lymph node and distant metastases of prostate cancer (PC) were analyzed. Further, mRNA expression data of metastatic PC were extracted from the Stand Up To Cancer–Prostate Cancer Foundation Dream Team database and differences between metastatic sites were comprehensively analyzed. CXC chemokine/receptor mRNA expression data of primary PC included in the Cancer Genome Atlas were used to analyze the relationships of CXC chemokine/receptor expression with lymph node metastasis and cancer progression. In metastatic PC, significantly higher expression of ELR+ CXC chemokines/receptors and significantly lower expression of ELR− CXC chemokines/receptors were observed in bone metastases relative to lymph node metastases. In primary PC, significantly higher ELR− CXC chemokine/receptor expression and significantly lower ELR+ CXC chemokine/receptor expression were observed in patients with lymph node metastasis relative to those without. Multivariate logistic regression analysis identified CXCL10 expression as an independent predictor of lymph node metastasis. Furthermore, the log-rank test results revealed that co-expression of CXCL10/CXCR3 was associated with postoperative recurrence. These findings demonstrate heterogeneous expression of CXC chemokine/receptor genes in primary PC as well as differences in expression patterns according to the metastatic site.